AN INTEGRATION: NARROW READING TO WEST’S GENERAL SERVICE LIST FOR VOCABULARY ACQUISITION FOR MIDDLE SCHOOL LEVEL - Ainun Fikria (IJET (Indonesian Journal of English Teaching), 2018)
Attempting to consider an SLA issues on vocabulary acquisition in middle school level, this article aimed to investigate the difference in score on vocabulary test of experimental and control group; and to find the effect size of the narrow reading integrated to West’s GSL intervention on students’ English language acquisition. Forty-five middle school students in two classes were assigned in two groups, with 22 students in the experimental group and 23 students in the control group. In addition to a traditional curriculum for both groups, a five-meeting narrow reading on narrative text, fable, which was integrated to West’s GSL was conducted for the experimental group by encouraging students to read using L1 gloss which was derived from GSL, consulting different meaning in some multi-definition content words and discussing on vocabulary exercise. In contrast, the control group did not engage in any narrow reading program but a general English course. A pretest and posttest of both groups were employed to collect data. The findings of the study showed that the intervention has a large effect size on student’s SLA. The experimental group exhibited significantly better reading comprehension, acquired new vocabulary and word knowledge than the control group. Therefore, applying narrow reading integrated to West’s GSL into EFL class helps improve students’ word knowledge in terms of recognizing word meaning, identifying part of speech and producing a sentence.